Falsely Identifying Original Sin and Pure Nature: Christological Implications - Henderson, Aaron (New blackfriars, 2021)
Robert Barry argues that man's condition in a state of pure nature and man's condition in the state of original sin are one and the same. This article aims to show that this thesis is false and is not the teaching of St. Thomas Aquinas. The Angelic Doctor teaches that man in pure nature would be more capable of doing the good proportionate to his nature and would be able to love God above all things with a natural love. Important here is the truth posited by many in the Thomist commentatorial tradition, namely, that on account of sin man is directly averted from his supernatural end and at least indirectly averted from his natural end. Furthermore, this thesis has undesirable consequences, albeit consequences unintended by Barry, for Christology and soteriology. We must understand what pertains to human nature as such if we are to understand the various states in which we find human nature, including in Christ. If a natural analogue to supernatural charity cannot even in principle obtain, charity will be something alien to human nature. Christ came not only to elevate us to supernatural life and divine friendship, but to heal human nature.